Analisis Potensi Pengembangan Ternak Babi Di Kecamatan Tenga Kabupaten Minahasa Selatan - Debora Kurnia Irianty Bunok; Yohannis L. R. Tulung; Nansi M. Santa (Sam Ratulangi University, 2022)
The purpose of this research was to identify and determine the potential for developing pigs in Tenga District, South Minahasa Regency and to formulate alternatives and determine priority strategies for developing pigs in Tenga District, South Minahasa Regency. The research instrument used in data collection was a list of questions (questionnaires) which were distributed directly to respondents and through direct interviews with farmers. The data were analyzed using SWOT analysis. The results showed that the implementation of a strategy that could be used in the development of pigs in Tenga District was the ST strategy where this strategy implemented Biosecurity in the pen area to prevent disease transmission so as to reduce economic losses, seek the location of the stables far from residential areas and seek the provision of septic tanks for waste storage so that environmental pollution does not occur, and look for more economical feed formulas as an option against uncertain feed prices so as to reduce high production costs.